Factors associated with induced abortion among women of reproductive age attending selected health facilities in Addis Ababa, Ethiopia: a case control study - Megersa, Bikila Soboka; Deckert, Andreas (BMC women's health, 2020)
There has been a significant reduction of abortion rates in high-income countries, while the rates remain unchanged in low- and middle-income countries. In Ethiopia, for example, the number of women of reproductive age seeking an induced abortion is increasing. However, there is limited information concerning the reasons why the occurrence of this procedure is increasing. Thus, this study aimed to identify factors associated with having induced abortion in Addis Ababa, Ethiopia.
Gesehen am 30.11.2020